Genetic and structural characterization of dengue virus involved in the 2023 autochthonous outbreaks in central Italy - Carletti, Fabrizio; Carli, Gabriella De; Spezia, Pietro Giorgio; Gruber, Cesare Ernesto Maria; Prandi, Ingrid Guarnetti; Rueca, Martina; Agresta, Alessandro; Specchiarello, Eliana; Fabeni, Lavinia; Giovanni, Elisa San; Arcuri, Chiara; Spaziante, Martina; et al. (Emerging microbes & infections, 2024)
Dengue virus (DENV) has been expanding its range to temperate areas that are not usually affected, where the spread of vectors has been facilitated by global trade and climate change. In Europe, there have been many cases of DENV imported from other regions in the past few years, leading to local outbreaks of DENV among people without travel history. Here we describe the epidemiological and molecular investigations of three transmission events locally acquired DENV infections caused by serotypes 1, 2 and 3, respectively, in the Latium Region from August to November 2023. Next-generation or Sanger sequencing was used to obtain the whole genomes, or the complete E-gene of the viruses, respectively. The structure of the DENV-1 and DENV-3 sequences was analysed to identify amino acid changes that were not found in the closest related sequences. The major cluster was supported by DENV-1 (originated in South America), with 42 autochthonous infections almost occurring in the eastern area of Rome, probably due to a single introduction followed by local sustained transmission. Seven DENV-1 subclusters have been identified by mutational and phylogenetic analysis. Structural analysis indicated changes whose meaning can be explained by the adaptation of the virus to human hosts and vectors and their interactions with antibodies and cell receptors.